Odporność drewna dębu szypułkowego (Quercus robur L.), z drzew o różnym stanie zdrowotnym, na rozkład powodowany przez grzyby - Szczepkowski, Andrzej (Leśne Prace Badawcze, 2010)
In the paper, natural resistance of wood of healthy and damaged common oak ( Quercus robur L.) trees to the activity of wood decaying fungi causing brown rot ( Coniophora puteana (Schumach.) P. Karst and Laetiporus sulphureus (Bull.) Murrill) and white rot ( Trametes versicolor (L.) Lloyd) was examined. The wood samples came from stands aged 60–147 years bearing signs of decline and excessive self-thinning of oak trees. The stands were located in 7 forest districts representing Poland’s main sources of oak wood. One healthy and one damaged sample trees were collected from each stand. Wood samples were cut out from outer heartwood at the butt-end of logs. The wood decay test was done according to the norm PN-EN 350-1. The mean width of annual rings and wood density were determined. In general, the wood of healthy trees was decayed to a larger extent than that of damaged ones by two test fungal species ( C. puteana and T. versicolor ), and in case of L. sulphureus the wood of damaged trees was decayed to the larger extent than the wood of healthy ones. The differences in loss of wood mass were not statistically significant. The loss of wood mass of healthy and damaged oak trees caused by C. puteana was 2.1 and 1.1%, by L. sulphureus – 7.0 and 7.7%, and by T. versicolor – 1.7 and 0.9%, respectively. Analysis of pairs of trees from three different forest districts (Czarna Białostocka, Miękinia, Mircze) showed somewhat lower resistance of the wood from damaged trees in comparison with healthy ones to the decay caused by three examined fungal species. The situation was the opposite for the two oak provenances of Jabłonna and Krotoszyn forest districts where the wood of healthy trees was less resistant than that of damaged ones. In case of wood from two other forest districts of Henryków and Wołów, no common tendency in decay of wood caused by all three fungal species was found. No geographical variability in loss of wood mass caused by the activity of the test fungi was found between healthy and damaged trees.